Análise das possibilidades e desafios do uso de reator solar para remover pesticidas em estações de tratamento de água - Pozeti, Gabriela Eloísa de Oliveira [UNESP] (2025)
With the increasing impacts associated with agricultural activities, pesticides are emerging as significant environmental contaminants, representing pressing public health challenges. Their presence has direct implications for the quality of surface and groundwater, which are often contaminated by processes such as leaching, aerial spraying, and deforestation along the banks of water bodies. This study aimed to present the effectiveness of advanced oxidation processes using CPC-type reactors for the removal of pesticides in water treatment plants. The implementation of CPC (Compound Parabolic Trough Collector) solar reactors constitutes an innovative solution, harnessing solar energy to catalyze chemical reactions, promoting the degradation of pesticides efficiently and sustainably. The relevance of this work transcends the scientific field, contributing to the promotion of public health and sustainable development, in line with the UN 2030 Agenda, particularly with Sustainable Development Goal number 6, which aims to ensure the availability and sustainable management of water and sanitation for all. The research highlights the benefits of integrating technological innovations in water treatment, promoting more sustainable and environmentally friendly practices in water resource management. This study is based on an extensive literature review, which supports the analysis of the possibilities and challenges of using CPC solar reactors for pesticide removal in water treatment plants. This approach allows for an in-depth understanding of the technological, environmental and methodological aspects involved, in addition to supporting the discussion of the results presented later. The results obtained indicate that the application of CPC solar reactors in water treatment plants can be a viable alternative to mitigate pesticide contamination, contributing significantly to water security and environmental quality. With methodological and applicability challenges that must be carefully considered and addressed to maximize their impact and relevance, this study reinforces the importance of continuing to invest in innovative and effective solutions for water resource management, essential for a healthier and more prosperous future.